Assessment in choosing higher education: a case of Indonesia / Dedy Ansari Harahap and Dita Amanah - Harahap, Dedy Ansari; Amanah, Dita (Universiti Teknologi Mara, Selangor: Puncak Alam Campus, 2019)
The decision of students to continue their studies is a decision after making considerations that are adjusted to the circumstances of a number of college choices. The purpose of this study is to examine the decisions of students to choose universities in Indonesia. The research method used is to compare the results of research and journals that examine students’ decision to choose a college. Then, examine the theories of consumer behavior so that it can be concluded what is considered by students. The results of previous studies show many influencing factors such as education costs, WOM, university reputation, location, lecture facilities, program accreditation and others. These results can be a reference and consideration for universities in Indonesia in attracting prospective students to choose certain universities and referring to others.